The 3 Dimensions of Digitalised Archaeology
XXI, 225 p. 99 illus., 58 illus. in color.
Keywords: This Open access book aims to provide an overview of state-of-the-art approaches to 3D documentation from a practical perspective and formulate the most important areas for future developments. Bringing together a wide range of case studies, examples of best practice approaches, workflows, and first attempts to establish sustainable solutions to pressing problems, this book offers readers current practical advice on how to approach 3D archaeology and cultural heritage. Divided into five parts, this book begins with an overview of 3D archaeology in its present state. It goes on to give insights into the development of the technology and recent cutting-edge applications. The next section identifies current challenges in 3D archaeology and then presents approaches and solutions for data management of a large number of 3D objects and ways to ensure sustainable solutions for the archiving of the produced data. This book will be of interest to researchers working in the fields of archaeology, heritage management, and digital humanities in general.